Direct numerical simulation of secondary flow in straight ducts forced by non-homogenous force - Martorana, Julia V. (2017)
Turbulent flow in ducts of rectangular section presents secondary flows due to the presence of turbulence. In this work we study this kind of turbulent flow driven by a non-uniform force in the vertical direction. This kind of forcing is used to model the stratification effect over the driving force of the flow. Of particular interest to this work are gravity currents, which are stratified flows generated by the gravity action over relatively small differences in density between two fluids. The fact that the flow is forced by the action of gravity on the density profiles causes the stratification effects to appear on two very different scales. On the microscopic scale stratification modulates turbulence and on the macroscopic scale stratification modulates the driving force of the flow. The objective of this work is to analyze separately the macroscopic effect of stratification inhibiting completely the microscopic effect of stratification. In this work, variations produced on secondary flow of the second kind when the flow is driven by forces that vary linearly and exponentially in the vertical direction are analyzed. These results are compared with the case of flow driven by an uniform force in the vertical direction. To this aim fully resolved direct numeric simulations are performed with a pseudo-spectral code.